2014
DOI: 10.1080/21663831.2014.963207
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Induced Short-Range Order Changes in Co67B33 Glassy Thin Films and Elastic Limit Implications

Abstract: In situ high-temperature X-ray diffraction experiments using high-energy photons and ab initio molecular dynamics simulations are performed to probe the temperature-induced changes in the topological short-range order in magnetron sputtered Co 67 B 33 metallic glass thin films. Based on this correlative experimental and theoretical study, the presence of B-Co-B rigid second-order structures at room temperature and the temperature-induced decrease in the population of these strongly bonded building blocks are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…For identifying the origin of ultrahigh stiffness in metallic glasses, we have studied the effect of an order of magnitude increase of the B to Y ratio in Co-Fe-Y-B thin film and melt spun metallic glasses on the elastic behavior, both theoretically and experimentally. It is observed that with increasing B to Y ratio from 1.8 to 10.2 the bulk modulus increases, which is consistent with previous reports on Co-B based metallic glasses [6,7,30,[37][38][39]. Using high energy x-ray diffraction experiments combined with DFT based molecular dynamics simulations, it is shown that the B induced increase in stiffness is dominated by the increase in metal to metalloid bond density and the concomitant increase in molar density.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For identifying the origin of ultrahigh stiffness in metallic glasses, we have studied the effect of an order of magnitude increase of the B to Y ratio in Co-Fe-Y-B thin film and melt spun metallic glasses on the elastic behavior, both theoretically and experimentally. It is observed that with increasing B to Y ratio from 1.8 to 10.2 the bulk modulus increases, which is consistent with previous reports on Co-B based metallic glasses [6,7,30,[37][38][39]. Using high energy x-ray diffraction experiments combined with DFT based molecular dynamics simulations, it is shown that the B induced increase in stiffness is dominated by the increase in metal to metalloid bond density and the concomitant increase in molar density.…”
Section: Discussionsupporting
confidence: 89%
“…3 B 20.9 metallic glass, which is consistent with the reduced pair distribution function analysis of figure 3(a). In literature strong metal to metalloid hybridization, associated with an increase in bond energy is proposed as the cause for the increase in stiffness observed for Co-B based glasses with increasing B content [6,7,30,[37][38][39]. From figure 3 we learn that the experimentally obtained short range order data from high energy x-ray diffraction and the predicted data are consistent.…”
Section: Comparison Of Stiffness and Short Range Order Between Simula...supporting
confidence: 68%
See 1 more Smart Citation
“…Pd 57.0 Al 23.9 Cu 11.4 Y 7.7 , Co 42.0 Fe 13.2 Zr 10.7 Ta 6.6 B 27.5 , Co 58.4 Fe 7.0 B 34.6 , Cu 67.8 Zr 32.2 and Co 68.3 Zr 31.7 metallic glass thin films were synthesised by physical vapour deposition59 by employing magnetron sputtering from 50 mm targets with a diameter of 50 mm using a ultrahigh-vacuum system59. Within this work, we report the synthesis and properties of the Pd 57.0 Al 23.9 Cu 11.4 Y 7.7 metallic glass thin film for the first time.…”
Section: Methodsmentioning
confidence: 99%
“…These results have e.g. been used to explain the temperature dependence of the elastic limit of Co-B metallic glasses 12 .
Fig.
…”
Section: Introductionmentioning
confidence: 97%